The Role of Teachers as Facilitators of Critical Learning: A Literature Review of Reflective Pedagogy Approaches in the 21st Century - Mufid Mufid (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study aims to analyze the role of teachers as facilitators in critical learning through a literature review on reflective pedagogy in the 21st century. A qualitative approach based on iterative studies was used to examine various empirical and conceptual findings relevant to modern pedagogical transformation. The results of the study indicate that teachers play a key role in guiding students towards critical thinking skills through structured, dialogic, and analytical learning strategies. Reflective pedagogy has been proven effective in increasing metacognitive awareness, evaluative skills, and a more systematic conceptual understanding. Previous studies have confirmed that reflective activities, directed discussions, and problem analysis are the most consistent approaches to supporting the development of critical thinking skills. In addition, teacher professional competence significantly influences the successful implementation of reflective pedagogy, especially in the aspects of managing learning interactions and developing evidence-based activities. This study also found that increasing teacher capacity and institutional support are important factors in strengthening critical learning practices. The literature synthesis provides a comprehensive overview of strategies that can be implemented to create a learning process that is more adaptive, collaborative, and relevant to the demands of the 21st century. This research provides a conceptual contribution to the development of reflective pedagogy and improving the quality of teachers' roles.